Student’s Digital Intentions Prediction Using CatBoost - Zulwisli; Ambiyar; Muhammad Anwar; Andhika Herayono (JTP - Jurnal Teknologi Pendidikan, 2025)
Digital Education and Entrepreneurial (DE) represents a new paradigm in Education and Entrepreneurial that leverages digital technology to create, manage, and expand businesses. By integrating advanced digital tools and platforms, DE plays a crucial role in reshaping traditional business models, driving innovation faster, and enabling enterprises to reach broader markets. This transformative approach benefits individual entrepreneurs and contributes to broader economic development. One of DE’s most significant impacts is its ability to foster economic growth. By embracing digital Education and Entrepreneurial, businesses can create new jobs, increase competitiveness, and adapt more effectively to the demands of the digital age. These factors collectively ensure that economies are better positioned to thrive in a technology-driven world. A recent study developed a predictive model using the CatBoost algorithm to understand better the factors influencing digital Education and Entrepreneurial. This advanced machine learning method was applied to data collected from thousands of college students, encompassing various demographic, psychological, and business-related variables. The results demonstrated the model’s high accuracy in predicting intentions toward digital Education and Entrepreneurial, offering a reliable framework for analysis and application. The study identified three key factors influencing students’ intentions to pursue digital Education and Entrepreneurial. These are digital skills, which reflect their ability to navigate and utilize digital tools effectively; self-efficacy, their confidence in their entrepreneurial capabilities; and Education and Entrepreneurial education, which equips them with the knowledge and skills needed to innovate and create businesses. These findings provide valuable insights for educational institutions and policymakers. By emphasizing digital skills training, fostering self-efficacy, and enhancing Education and Entrepreneurial education programs, they can better prepare students to succeed in the digital economy. Such targeted initiatives empower individuals and contribute to the sustainable growth of digital Education and Entrepreneurial, reinforcing its role as a driver of innovation and economic progress.